Simulation of helicopter aerodynamics in the vicinity of an obstacle using a free wake panel method - Schmid, M. (My University, 2017)
In the present paper the influence of a helicopter wake on an idealized obstacle and vice versa is investigated. Simulations made by using an unsteady panel method are compared to experimental results from a wind tunnel test campaign. Various positions relative to the obstacle and two different wind conditions are investigated. A very good accordance of the panel method to the experimental data can be shown for most of the test cases without wind. Only those positions where the helicopter rotor is in a recirculating flow field differ from the measured values. For the test cases under head wind condition the accordance is not as good as without wind. Here the flow regions under influence of viscous effects are wider and the predictions made by the panel method have larger offsets.